The simulation of aerosol Lidar developed at the Institute of Geophysics - Tuan, A. D.; Anh, N. X.; Hung, T. P. (Vietnam Journal of Marine Science and Technology, 2017)
Lidar is an active remote-sensing system that uses laser radiation in the ultraviolet, visible and near-infrared wavelength domain. It allows the measurement of the physical properties of the atmosphere with spatial and temporal resolution. We have simulated the system and researched the initial design of the Lidar system to monitor the aerosol with the main parameters: high power Nd - YAG pulse laser emitted at the 532 nm wavelength. The system includes 28 cm diameter optical glass, photomultiplier tube (PMT) - H6780-03 photodetector, and optical components for convergence and filtering of reflected reflections. Initial measurements show that the Lidar system is highly sensitive, which determines important atmospheric properties such as the distribution and physical properties of the aerosol and height of ABL (atmospheric boundary layer).